2011
DOI: 10.1007/s11033-011-0751-0
|View full text |Cite
|
Sign up to set email alerts
|

Are biomarkers correlated with recurrence patterns in patients with resectable gastric adenocarcinoma

Abstract: The aims of this study are to analyze the failure patterns in radical resected gastric adenocarcinoma, and to evaluate the correlation between recurrence patterns and potentially prognostic factors, including clinical pathological characteristic and biomarkers. Between Jan 2004 and Jun 2006, 84 patients were enrolled into the database analysis, including 8 with clinical stage I, 20 with clinical stage II, 21 with clinical stage IIIA, 22 with clinical stage IIIB and 13 with clinical stage IV, male 61 and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…However, our results showed that Ki-67 overexpression is related to recurrence and metastasis of MECs. Our study results are in accordance with Li et al who found that Ki-67 was correlated with lymph node metastasis and was not correlated with prognosis [24]. Our results support the model of carcinogenesis, with increased loss of control of cellular proliferation with the accumulation of genetic alterations in dysplastic lesions.…”
Section: Discussionsupporting
confidence: 91%
“…However, our results showed that Ki-67 overexpression is related to recurrence and metastasis of MECs. Our study results are in accordance with Li et al who found that Ki-67 was correlated with lymph node metastasis and was not correlated with prognosis [24]. Our results support the model of carcinogenesis, with increased loss of control of cellular proliferation with the accumulation of genetic alterations in dysplastic lesions.…”
Section: Discussionsupporting
confidence: 91%
“…EGFR expression correlates with disease recurrence and poorer survival [28]. This is substantiated by other studies as well in which EGFR overexpression is associated with an aggressive tumor and also with lymph node metastasis [39]. EGFR dimerization and activation leads to downstream upregulation of multiple processes that can result in cancer cell proliferation, reduced apoptosis, tumor-induced angiogenesis, and activation of invasion, dedifferentiation of cancer cells and enhanced metastatic potential [40,41].…”
Section: Discussionmentioning
confidence: 78%
“…Of note, different patterns of recurrence correspond to different postoperative adjuvant therapy regimens. Hence, it is signi cant to predict the recurrence pattern to scheme personalized therapy [21] . Previously, Huang et al reviewed the medical records of 317 node-negative GC patients and the results showed that 51 patients had recurred, the population patients with locoregional recurrence, peritoneal seeding accounted for 51.0% separately and 21 (41.1%) patients had hematogenous metastasis [15] .…”
Section: Discussionmentioning
confidence: 99%